ChemInform Abstract: Radical Cyclizations of Cyclic Ene Sulfonamides Occur with β‐Elimination of Sulfonyl Radicals to Form Polycyclic Imines. Issue 19 (13th May 2014) - Zhang, Hanmo; Hay, E. Ben; Geib, Steven J.; Curran, Dennis P.
Abstract The title reaction affords fused and spirocyclic imines with five‐, six‐ and seven‐membered rings.